A gestão da informação como instrumento para prática da organização documental: pesquisa-ação aplicada à Coordenação de Assessoria a Gestão e Informações (CAGES) do Banco da Amazônia - BARBOSA, Roberta Suellen Mesquita (2018)
It seeks to ascertain the organization of three types of documentary publications produced by the Management and Information Management Coordination (CAGES), belonging to Bank of the Amazon. In this direction, the objective is to know how the organization process occurs, and what motives led to the need to apply the procedures and tools directed by information management, as well as to portray its possible practical advantages. Starting from the action - research, field observation is used and as object of study, three official documents with continuous production are used, namely: (1) Minutes of COMIR Meeting; (2) COMET term of adhesion; (3) Administrative Inquiries established or to be instated by CGU-PAD.. The results point to a number of benefits to the sequential and ordered production of documents, in addition to the recovery, dissemination and corporate collaboration when linked to information management, making it an instrument that certainly standardizes the internal documentation process. Thus, the importance of using management is emphasized by the fact that the corporate community of CAGES is integrated with the production, registration, publication and documentary storage crucial to the Bank of the Amazon, establishing new perspectives regarding the information produced for the proper functioning of the services and products of the institution.